ENHANCING WOMEN’S ECONOMIC ACTIVITY IN UZBEKISTAN: A LEGAL AND INSTITUTIONAL ANALYSIS - Dilafruz Majidova (Ecominds Press, 2025)
The article analyzes the legal and institutional foundations of state policy aimed at promoting gender equality and enhancing women's economic activity in Uzbekistan. It examines the role of women’s professional training, participation in entrepreneurship, access to credit resources, and the effectiveness of state programs since the 1990s. Presidential decrees and regional programs are evaluated as key instruments in strengthening women’s participation in the labor market and improving their social status.
Keywords: Gender equality, women’s policy, entrepreneurship, legal framework, economic activity.